Faktor Risiko Kejadian Rinitis Alergi pada Anak - Intan Nurhaliza Nurhaliza; Mukhlis Imanto (CV. Jasa Sukses Abadi, 2023)
Allergic rhinitis is one of the global health problems that affect about 400 million people in the world with prevalence of 8.38% in children and 14.93% in adolescents, in Indonesia the incidence of allergic rhinitis reaches 38%. Allergic rhinitis is a clinical symptom that occurs when the nasal mucous membrane is exposed to an allergen and induces an immune system-mediated inflammatory response. Allergic rhinitis can be triggered by several factors, including individual and environmental factors that can lead to resensitization and disease progression. The main risk factor for allergic rhinitis is family history of atopy, especially history of allergic rhinitis in both parents. The presence of atopic dermatitis, asthma, exposure to vehicle acids, cigarettes and house dust, obesity can be factors that increase the risk of allergic rhinitis in children. These risk factors have their respective mechanisms in increasing the risk of allergic rhinitis and have different levels of risk. Other factors such as gender and age did not contribute to increasing the risk of allergic rhinitis in children.